Urban Network in Trade and Tourism City Case Study: Pontianak City, Indonesia - Syaiful Muazir (The Institute for Research and Community Services, Institut Teknologi Bandung, 2018)
Abstract. Pontianak City is the capital of West Kalimantan Province, Indonesia. In contributing to one of its missions to be a city that supports the development of trade,services and tourism, Pontianak continues to make improvements through physical development and spatial arrangement to maintain the flow of goods and services. The purpose of this study was to analyze the existing urban networks (in this case infrastructure networks) in Pontianak in support of the city's development goals to become a leading trade, services, and tourism center in Kalimantan. Network analysis was applied by analyzing the infrastructure networks, explore the 'structural position' and then the tendency of the infrastructure network configuration in connecting the trade/market areas or tourist attractions was investigated. Based on the analysis, it was found that the central or important areas that link other areas within the infrastructure network configuration are still dominated by market or trading areas/functions, while for tourist attractions they are still limited. Increased centering or grouping in specific areas can be achieved by adding or reducing the degree of connectedness, by arranging the flow or connections (links) from one area (point) to another, directly or indirectly, with the infrastructure network as the intermediary.Keywords: urban, network, trade, tourism, PontianakAbstrak. Kota Pontianak adalah ibu kota provinsi Kalimantan Barat, Indonesia. Dalam mendukung salah satu misinya sebagai kota yang mendukung pengembangan perdagangan dan jasa, Pontianak terus melakukan perbaikan melalui perkembangan fisik dan tata ruang untuk menjaga arus barang dan jasa. Tujuan dari penelitian ini adalah untuk menganalisis jaringan perkotaan yang ada (dalam hal ini adalah jaringan infrastruktur) di Pontianak dalam mendukung tujuan pembangunan kota untuk menjadi kota perdagangan, jasa, dan pariwisata terdepan. Analisis jaringan diaplikasikan dengan menganalisa jaringan infrastruktur, mengeksplorasi 'posisi struktural', dan kemudian menggambarkan kecenderungan konfigurasi jaringan infrastruktur dalam menghubungkan wilayah perdagangan/pasar atau tempat wisata. Berdasarkan analisis tersebut, didirikanlah kawasan sentral atau penting yang menghubungkan daerah lain dalam konfigurasi jaringan infrastruktur yang masih didominasi oleh pasar atau wilayah/fungsi perdagangan. Sedangkan untuk tempat wisata, masih terbatas. Untuk meningkatkan keterpusatan atau pengelompokkan untuk area tertentu, dapat dilakukan dengan menambahkan atau mengurangi tingkat keterhubungan, dengan mengatur aliran atau koneksi (link) dari satu area (titik) ke titik lainnya; secara langsung atau tidak langsung, dengan jaringan infrastruktur sebagai perantara.Kata Kunci: perkotaan, jaringan, perdagangan, pariwisata, Pontianak